2000
DOI: 10.1679/aohc.63.33
|View full text |Cite
|
Sign up to set email alerts
|

The Expression and Cellular Localization of the Sperm Flagellar Protein MC31/CE9 in the Rat Testis. Possible Posttranscriptional Regulation during Rat Spermiogenesis.

Abstract: We isolated the MC31 cDNA clone coding the antigen specifically recognized by the monoclonal antibody mMC31, and found that MC31 was identical to rat CE9. Therefore, this molecule is called MC31/CE9. MC31/CE9, a member of the immunoglobulin superfamily molecules, was localized on the rat sperm flagellar plasma membrane. We analyzed the expression and cellular localization of MC31/CE9 mRNA and protein in the adult rat testis by use of Northern hybridization, in situ hybridization, and immunohistochemical analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…At steps 11-13, it appears on the whole tail and then redistributes to the posterior tail between steps 13 and 14 and during spermiation. CE9 redistributes along the tail coincident with the caudal migration of the annulus late in spermiogenesis (Cesario et al, 1995;Toshimori et al, 2001;Wakayama et al, 2000).…”
Section: Proteins Found In Different Flagellarmentioning
confidence: 99%
“…At steps 11-13, it appears on the whole tail and then redistributes to the posterior tail between steps 13 and 14 and during spermiation. CE9 redistributes along the tail coincident with the caudal migration of the annulus late in spermiogenesis (Cesario et al, 1995;Toshimori et al, 2001;Wakayama et al, 2000).…”
Section: Proteins Found In Different Flagellarmentioning
confidence: 99%
“…We recently found that MC31 is homologous to CE9, based on cDNA analysis [49]. However, the results are somewhat different from that of CE9, probably due to differences in the epitope or antibody raised.…”
Section: Sperm Flagellar Plasma Membrane Proteinsmentioning
confidence: 96%
“…An in situ hybridization study of the MC31/CE9 mRNA expression showed that the mRNA is first found in leptotene spermatocytes throughout their development to elongated spermatids [49]. The protein is initially expressed in leptotene spermatocytes to testicular sperm [33], which is basically the same as that of CE9 [54].…”
Section: Sperm Flagellar Plasma Membrane Proteinsmentioning
confidence: 97%
See 1 more Smart Citation
“…These processes induce the reorganization of membrane proteins, with the relocation or reorganization within or across the domain(s), as evidenced by immunostaining pattern changes. Such cases are typically found in the ADAM or MDC protein (ADAM family, Primakoff and Myles, 2000;Blobel, 2000;MDC family, Frayne et al, 1998) and in some membrane proteins belonging to the immunoglobulin superfamily (CE9, Petruszak et al, 1991;Cesario and Bartles, 1994; MC31(CE9), Toshimori et al, 1992;Wakayama et al, 2000;basigin, Saxena et al, 2002).…”
Section: Overviewmentioning
confidence: 99%